PROBLEMATIKA KEDUDUKAN ANAK ANGKAT DALAM MENERIMA HARTA WARISAN DAN PENYELESAIANNYA MENURUT KOMPILASI HUKUM ISLAM (KHI) - Siti Nuraenun (UIN Siber Syekh Nurjati Cirebon, 2017)
AbstactThe adopting of children and adopted children is part of substation from law of children safety which were be part from the law winch life and flourish in civil society in accordance with the usually and the different motivation and feel of law winch life and flourish in any area. Therefore, the case of children adoption must be regulated in specific in constriction that.From commentary about that can formulation case as follows: (1) How is the position adopted children in farting of heritage according to heritage KHI? (2) if haven’t the dispute about heritage treasure, how the solution? The kind of this research is descriptive qualitative, where is the releaser is mean to know the condition about what, how, and to par, how much and etc. with the description result data research with word by word or the separated sentence according to category and analysis for getting the conclusion.With this research writer will be describing clarity the position of children in Islamic Law Compilation (KHI). The kind of research use the research library while the technique of analysis is with to find and analysis references primer and secondary. The result of research, is: (1) the definition of adopted children too and there to there are in pasal 171 huruf h KHI which declare that adopted children is the children which in the nurture for the daily of them life, the case of education and any other switch the responsibility from the pure parent to adopted parent by the justices jurisdiction (2) the adoption of children according to KHI not because the justice relation of generation or the blood a child with his / her parent who born. (3) Accomplishment the dispute in family law, in this case marriage and the heritage still be authority of Islamic justice.The suggestions is: (1) in order to the Islamic civil society in Indonesia who want or were do adoption of children suggested to study about the provision of Islamic law use any books about adoption of children so that get the reference about the role of children adoption in al-Qur’an or Hadits. (2) in order to the adopted parent preparation all about the necessary of adopted children is especially about the case of education, welfare and the healthy from now and make a massage in from of the witness, in order to later if the adopted parent is death and leave the heritage, no to inflict the conflict between adopted children and heir from adopted parent.Keyword:Adopted Children, Haritage